PENGARUH OSILASI TAHUNAN DAN ENSO TERHADAP VARIABILITAS OZON TOTAL INDONESIA - Ambarsari, Novita; Yulihastin, Erma (Teknologi Indonesia, 2011)
The global ozone data of TOMS (Total Ozone Mapping Spectrometer) from NASA (National Aeronautics and Space Administration) Satellite was used from 1997 to 2005 in Indonesia (90E-151.2E, 12.5S-12.5N). The results of time series total ozone concentration data showed that the concentration varied from 242 to 275.38 Dobson Units. The highest concentration occurred from September to October, which was period of transition season from dry to rainfall season in Indonesia. In that times occurred autumn in northern hemisphere. The lowest concentration occurred from December to February, which was period of peak rainfall season in Indonesia, besides winter in northen hemisphere. The spectral analysis used FFT (Fast Fourier Transform) method founded total ozone variability in Indonesia from 1997 to 2005 was dominant infl uenced by annual oscillation (period of 11.33 months), ENSO (25.5 months), and semiannual oscillation (5.67 months).